Lightning Performance and its Prevention for Quadruple-circuit Transmission Line with 220kV/110kV Voltage in a Tower - Li Chunhua; Wang Weiran; Su Jie; Li Tao (Institute of Advanced Engineering and Science, 2013)
According to the physical process of discharge development of insulator that is struck by lightning, the lightning flashover model for quadruple-circuit transmission line with dual voltage 220kV/110kV in same tower is established basing on EMTP. The actual evaluation index of lightning protection performance is adopted with the consideration of influence of system voltage. The characteristics of multi-circuit trip-out simultaneously for mixed-voltage lines in same tower is studied, and the distinctions of lightning protection performance caused by differentiated configuration mode of lightning protection measures including phase sequence arrangement, coupling ground wire and so on. The results indicate that the lightning withstand level fluctuates approximately with the phase angle in the form of non-standard sinusoidal wave. The lightning withstand level emerges as optimum performance under the completely reversed phase sequence. The effect of coupling ground wire on top of tower is superior to that on bottom. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3413